Analisis Pelayanan Rumah Sakit dr. Bratanata Jambi Selama Pandemi Covid-19 - Bettrianto Bettrianto; Vina Dwi Lestari; Anipah Anipah (STIKES Garuda Putih, 2024)
Pandemic (COVID-19) is a problem that is being faced in more than 200 countries around the world. Our country, Indonesia is also badly affected by COVID-19 where the death rate reached 8.9% at the end of March 2020. Based on data from the Task Force in Indonesia, on January 26, 2021 there were 1,012,350 positive cases, 820,356 recovered and those who died as many as 28,468 people. In South Sumatra the number of cases was 13,911. The Lahat district of South Sumatra, 547 positive data were obtained, 571 suspected, 23 probable, with 507 recovered cases, 33 died. The increase in the number of confirmed COVID-19 cases is increasingly making the Lahat community to seek treatment at the hospital to be of particular concern. The current development situation that is always changing can create opportunities or even become a threat to other health care hospitals. One of the efforts to find out the right strategy for the hospital is a SWOT analysis. This study explains the SWOT analysis at TK III.02.06.01 Dr.Bratanata Jambi Hospital with combined qualitative and quantitative research methods based on SWOT analysis and a matrix. IFE and EFE with descriptive analysis methods. The data sources were obtained from primary data and secondary data at TK III.02.06.01 Dr.Bratanata Jambi Hospital. The results of this study stated that the total strength was 2.41; weakness 1.41; odds 2.53 and threats 1.45. The strategic position of the TOWS diagram is in the upper right quadrant I or aggressive position. The hospital's strategy is to make the hospital a referral place for COVID-19 patients and collaborate with the private sector and the government.